Design of a personalized oral‒motor exercise device for speech impairment rehabilitation - Woo, Seong Tak; Ha, Ji-Wan; Na, Sungdae (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction: Dysarthria is a speech disorder that stems from impaired muscle control due to lesions in the articulatory system, necessitating targeted rehabilitation exercises to strengthen affected muscles. Current devices used for rehabilitation often fail to accurately assess exercise execution, which limits their effectiveness.Methods: This study introduces a novel oral-motor rehabilitation device designed to overcome these limitations. The device features flexible sensors and a signal processing module that provides real-time feedback on training intensity. It is integrated with a mobile application that enables users to monitor their tongue’s range of motion and track their progress through a calibration process that uses a simple moving average filter. A preliminary study was conducted with five healthy adult male subjects to verify the device’s basic operational characteristics.Results: The effectiveness of the device in improving muscle function and regulating training intensity was evaluated using the Iowa Oral Performance Instrument. The results showed promising outcomes in enhancing articulation and oral-motor skills, indicating that the device could effectively contribute to dysarthria rehabilitation.Discussion: By addressing the gaps in current rehabilitation practices for dysarthria, the proposed device offers a comprehensive and personalized approach to oral-motor therapy. Its ability to provide immediate feedback and track progress can significantly enhance the rehabilitation process, potentially leading to better outcomes for patients with dysarthria.